Editorial - Mensah Danquah, Monica (Ghana Library Journal, 2024)
I am pleased to present the Volume 29, issue1 of the Ghana Library Journal. In this issue of the journal, the editorial team has curated a selection of articles that showcase the latest developments, trends, and best practices in Library and Information Science with the goal of informing and inspiring our readers. As the automobile industry continues to embrace technological advancements, mechanics in Ghana are having to adapt their information-seeking behaviors to keep up with the technology. This shift has significant implications for the way we approach knowledge sharing and skill development in the industry. The first paper by Asare, Adu and Mills hence set out to explore the impact of technological trends on the information-seeking behaviors of mechanics in Ghana and argue for increased investment in digital training and resources.